Performing the Cold War in the Postcolonial World : Theatre, Film, Literature and Things. - Balme, Christopher B. (Milton : Taylor & Francis Group, 2023)
This volume explores how the Cultural Cold War played out in Africa and Asia in the context of decolonization. Both the USA and the Soviet Union as well as East European states undertook significant efforts to influence cultural life in the newly independent, postcolonial world.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books